A generic π* shape resonance observed in energy-dependent photoelectron angular distributions from two-colour, resonant multiphoton ionization of difluorobenzene isomers - Staniforth, Michael; Daly, Steven; Reid, Katharine L.; Powis, Ivan (American Institute of Physics, 2013)
We present new evidence for the existence of a near threshold π* shape resonance as a common feature in the photoionization of each isomer of difluorobenzene. Experimentally this is revealed by significant changes in the anisotropy of the photoelectron angular distributions (PADs) following the ionization of the optically aligned S1 state of these molecules at varying photon energies. Continuum multiple scattering Xα calculations reproduce this behaviour well and allow the visualisation of the continuum shape resonances. The resonances are unusually narrow in energy (<1 eV) but nevertheless appear to extend right down to the ionization thresholds—exactly the low energy range typically accessed in laser-based resonance enhanced multiphoton ionization (REMPI) schemes. The anticipation of such pronounced energy dependence in the PADs and cross-sections sought for other molecules and an ability to accurately predict such features should be important for the reliable application and interpretation of experiments involving REMPI probing of those molecules.